Gnotobiotic Plant Systems for Reconstitution and Functional Studies of the Root Microbiota. Issue 2 (4th February 2022) - Ma, Ka‐Wai; Ordon, Jana; Schulze‐Lefert, Paul
Abstract: Healthy plants host a multi‐kingdom community of microbes, which is known as the plant microbiota. Amplicon sequencing technologies for microbial genomic markers were a milestone in revealing the taxonomic composition of the microbiota and its variation associated with a plant host in natural environments. However, this method alone does not allow conclusions to be drawn about functions of these microbial assemblages for the plant. The development of culture collections, which recapitulate natural microbial communities in their diversity, and multiple gnotobiotic plant systems therefore represent a breakthrough in plant‒microbiota research such that plants can be inoculated with defined communities to study proposed microbiota functions. These systems provided, for the root microbiota, first insights into mechanisms underlying microbial community establishment and contributions of its microbial members to indirect pathogen protection and mineral nutrition of the host. We argue that the choice of a gnotobiotic system for microbiota reconstitution and subsequent functional analysis depends on the particular plant trait that is influenced by the microbiota. We start by discussing the advantages and limitations of using individual gnotobiotic systems and then describe the general procedures for preparing bacterial cultures from the Arabidopsis thaliana At ‐R‐SPHERE culture collection for inoculation and cocultivation in two gnotobiotic plant growth systems using agar and perlite matrix. Additionally, a protocol for inoculation of plants with opportunistic Pseudomonas pathogens is provided. Lastly, we describe a high‐throughput system for visual assessment of roots after inoculation with individual mutants of a transposon library generated from a root‐derived bacterial commensal. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of bacterial cultures from At ‐R‐SPHERE Support Protocol 1 : Validation of strains by sequencing hypervariable regions of the 16S rRNA gene Basic Protocol 2 : Coinoculation of plants grown on an agar matrix with microbial elicitor and a defined microbial community Alternate Protocol : Inoculation of plants cultivated in a perlite‐based growth system Support Protocol 2 : Surface sterilization of Arabidopsis thaliana seeds Basic Protocol 3 : Inoculation using a Pseudomonas opportunistic pathogen Basic Protocol 4 : Assessment of commensal‐mediated root phenotypes using phytostrips